Severance pay and solidarist associations: a financial perspective - Solé Madrigal, Roberto (2013)
Employee Associations have had a considerable growth in our country over the past decades. However, the legal treatment given to employers’ contributions of unemployment compensation which are monthly transferred to the Employees Associations, and which are seen as simple unemployment insurance’ advance payments, causes an incremental employer’s contingency in that matter. this is when a worker is fired without a fair cause, and thus, with all its unemployment rights, including unemployment compensation. This work tries to put on perspective the financial side of the relationship between the unemployment compensation and the Employee Associations, simulating and quantifying the contingency mentioned.